2020
DOI: 10.1089/jayao.2019.0134
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Services for Adolescents with Cancer in Italy: Access to Pediatric Oncology Centers and Dedicated Projects

Abstract: Purpose: To describe how the provision of services for adolescents with cancer has evolved in Italy, the study evaluated access to pediatric oncology centers affiliated to the national cooperative group Associazione Italiana Ematologia Oncologia Pediatrica (AIEOP), and the development of dedicated local projects. Methods: We calculated the observed/expected (O/E) ratio of adolescent patients (15-19 years old) admitted to AIEOP centers during the years 2013-2017. Observed cases were obtained from the AIEOP data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…Over the 20 years, adolescent enrollment in AIEOP centers progressively grew from 16.1% of MH’96 patients to 32.9% of LH2004 patients ( p = 0.000). This reflected a similar increase reported in AYAs with lymphoma and other cancers treated with AIEOP protocols in Italy in the same time span [ 14 , 15 , 16 ]. This trend was also seen in North America, with 16–21 AYAs: from 28% in POG-9426 between 1996 and 2005, to 38% in COG-AHOD0431 between 2006 and 2009 [ 17 ].…”
Section: Discussionsupporting
confidence: 79%
“…Over the 20 years, adolescent enrollment in AIEOP centers progressively grew from 16.1% of MH’96 patients to 32.9% of LH2004 patients ( p = 0.000). This reflected a similar increase reported in AYAs with lymphoma and other cancers treated with AIEOP protocols in Italy in the same time span [ 14 , 15 , 16 ]. This trend was also seen in North America, with 16–21 AYAs: from 28% in POG-9426 between 1996 and 2005, to 38% in COG-AHOD0431 between 2006 and 2009 [ 17 ].…”
Section: Discussionsupporting
confidence: 79%
“…Clearly a multifaceted strategy is required to improve AYA recruitment into clinical trials, with substantial modification of the traditional approaches to drug development, regulation, protocol development and care environments. [42][43][44][45][46][47][48][49][50][51] These processes will themselves benefit from greater specialisation and interdisciplinary cooperation. The main challenges of access to clinical trials are summarised in Table 3.…”
Section: Characteristics and Challenges Of Aya With Cancermentioning
confidence: 99%
“…One such recent study, referring to 2013–2017, and to 9534 cases registered in the AIEOP database (8031 patients aged 0–14 and 1503 aged 15–19 years), reported an observed/expected (O/E) ratio of 0.81, but it was 1.06 for children and just 0.37 for adolescents (as well as differing significantly by type of tumor). 14 In other words, this study showed that practically all children with cancer in Italy were treated at AIEOP centers, but the same could not be said of the older adolescents. Such an evident gap in access to care, and to clinical trials for adolescents with cancer, is an internationally recognized challenge.…”
Section: Discussionmentioning
confidence: 71%
“…15,16 Some progress has been made, however: the percentage of adolescents treated at AIEOP centers has increased over the years, with the corresponding O/E ratio rising from 10% in 1989–2006 17 to 28% in 2007–2012, 18 and to 37% in 2013–2017. 14…”
Section: Discussionmentioning
confidence: 99%